Islam in Malaysia An Entwined History - Khairudin Aljunied (Cendekia, 2019)
Islam has maintained its presence in Malaysia for over a millennium, giving rise to highly pluralized and complex communities. In this richly textured portrait, Khairudin Aljunied explores the overlapping waves of Islamization and conversion in Malaysia across ten centuries, through the Hindu-Buddhist period, the age of Muslim kingdoms, the colonial interregnum, and the contemporary era. The book offers a new approach to studying Malaysian Islam-entwined history-that will be useful for scholars specializing in historical Islam in other contexts. It is an approach that considers how states and societies, scholars and ordinary Muslims, and, more crucially, non-Muslims have all contributed to the embedding of Islam in the everyday lives of Malaysians. Providing a gripping and sophisticated account of these various driving forces, Aljunied also explores the roles of global movements and currents of thought, offering perceptive insights into how local actors appropriated and reinterpreted a world religion to suit their unique customs and circumstances. Islam in Malaysia: An Entwined History is at once an original and an authoritative take on the manner in which Islam has been infused, lived, expressed, enforced, and debated in one of the world's most developed Muslim-dominated nations.